DEVELOPMENT OF FLIPBOOK-BASED TEACHING MATERIALS ON BASIC TECHNICAL ELEMENTS OF OFFICE ACTIVITIES - Khairanni, Sarah; Wibowo, Agus; Adha, Maulana Amirul (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This study aims to assess the feasibility and practicality of developing flipbook-based teaching materials for Basic Technical elements of Office Activities in the Field of Office Management and Business Services. Conducted at Public Vocational High School 31 Jakarta in 2024, the study involved 36 class X Office Management (MP) students. Utilizing the Research and Development (R&D) approach with the ADDIE framework model (Analyze, Design, Development, Implementation, Evaluation), the study included three validators: material, language, and media experts, alongside the students as respondents. Data collection utilized a quantitative approach with a Likert scale questionnaire (1-5). Expert validation and practicality tests were conducted, showing results of 89% (very feasible) by material experts, 91% (very feasible) by language experts, and 88% (very feasible) by media experts. Practicality tests by students indicated 88% (very practical) in one-to-one evaluation, 90% in small group trials, and 92% in large group trials. The study shows that the developed flipbook is highly feasible and practical for learning activities.